Emergent integration: the creation of an enlarged European Automobile Space under institutional uncertainty. (6th January 2009) - Van Tulder, Rob
The 2004 enlargement of the European Union with ten new member states represents a problem of 'emergent integration' – the creation of new institutions under sizable degrees of uncertainty. This paper specifies three types of uncertainty (entry, institutional and strategic uncertainty) and assesses to what extent these uncertainties have influenced the position of the new member states in a particular regional division of labour. The paper documents and illustrates the dynamic interaction of firm and government strategies and their outcome for a sector that contains important 'agents of change' and the largest foreign direct investors in most Central and Eastern European (CEE) countries – the car industry.